2017
DOI: 10.2147/cia.s137993
|View full text |Cite
|
Sign up to set email alerts
|

Social participation and perceived depression among elderly population in South Africa

Abstract: There is a growing consensus regarding the influence of various psychosocial factors such as degree of social participation on health and disease outcomes, quality of life, and general well-being. Older individuals with diminished motor and physical functionality suffer a heightened risk of social exclusion and loneliness. Previous studies have demonstrated the association between social exclusion and loneliness with mental health among the older population. In the present study, we aimed to investigate whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 17 publications
3
47
0
6
Order By: Relevance
“…Social participation was perceived by the participants as a means for involvement in the local community and staying active and engaged and, consequently, for giving meaning. Social participation seemed to play a role in the mental health and well-being of older persons, which is in line with the ndings from other studies (51)(52)(53)(54). Social participation may contribute to health by helping to maintain social contacts, providing a sense of meaning in older persons' lives and a sense of belonging to a social group and context, as well as increasing access to social support (43,51,52,55).…”
Section: Discussionsupporting
confidence: 86%
“…Social participation was perceived by the participants as a means for involvement in the local community and staying active and engaged and, consequently, for giving meaning. Social participation seemed to play a role in the mental health and well-being of older persons, which is in line with the ndings from other studies (51)(52)(53)(54). Social participation may contribute to health by helping to maintain social contacts, providing a sense of meaning in older persons' lives and a sense of belonging to a social group and context, as well as increasing access to social support (43,51,52,55).…”
Section: Discussionsupporting
confidence: 86%
“…Self-reported depression was assessed by the question: “During the last 12 months, have you had a period lasting several days when you felt sad, empty or depressed? [ 23 25 ]” The answers were kept as a binary response: “Yes” and “No”. Quality of life was also measured subjectively by the question: “How would you rate your overall quality of life?” with the answers being: Very Good, Good, Moderate, Bad, Very Bad.…”
Section: Methodsmentioning
confidence: 99%
“…Under the umbrella concept of structural/cognitive social capital (Harpham et al, 2002;Hikichi et al, 2018), prior literature suggested that social interaction/communication during participating in social activities may incentivize mutual support, and provide one with a sense of belonging and largely reduce social isolation (Hikichi et al, 2017;Lin et al, 1999), which therefore, may improve mental health or prevent depression (Almedom, 2005). However, as SP covers a wide range of social activities, limited studies have revealed that the direction of the association and the magnitude varies between different types of activity, but failed to reach an agreement on the type or amount of SP that is associated with lower odds of depression (Hao et al, 2017;Roh et al, 2015;Vogelsang, 2016). One potential underlying reason may be that the social significance of SP varies amongst specific types and across the cultural contexts of investigation (Chiao et al, 2011).…”
Section: Introductionmentioning
confidence: 99%